The Dynamics Of Learning Difficulties Among Students At Islamic Boarding Schools In The Digital Age: Between Tradition And Technological Limitations - Muhammad Arrafi Muzhaffar Permadi; Wahyudin Khairul Syaban; Muhammad Ikhsan Habibi; Fauzi Purnama; Senja Ampera (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to reveal the dynamics of learning difficulties faced by students in traditional Islamic boarding schools in the digital age, which are caught between the preservation of Islamic values and the demands of technological modernization. Using a qualitative approach with a case study strategy, data was collected through in-depth interviews and focus group discussions with 15 senior high school students from various majors and levels of education. The results of thematic analysis show four main findings: technological limitations that impact access to learning resources; conventional teaching methods that are less adaptive to digital learning styles; differences in students' views on the integration of technology in learning; and adaptive strategies used by students through collaboration, informal discussions, and the utilization of limited resources. These findings reinforce the relevance of the Digital Divide and Social Constructivism theories in the context of Islamic education, emphasizing that the digital divide in Islamic boarding schools is not merely a matter of infrastructure, but also a matter of values and learning culture. The novelty of this research lies in its focus on the agency of students as adaptive actors in the transformation of Islamic education, showing that Islamic boarding schools have the potential to develop hybrid learning models that harmonize tradition and technology.